Antecedent infections, recent developments and future directions in Guillain-Barré syndrome - Iqbal, Rashid; Asad, Muhammad Javaid; Mahmood, Raja Tahir; Shah, Muhammad Basir; Nawaz, Zahida; Siddiqi, Saima (Journal of the Pakistan Medical Association, 2022)
The Guillain-Barré syndrome is an autoimmune polyradiculoneuropathy causing symmetrical weakness of limbs. After poliomyelitis, it is the second most common cause of paralysis, with an annual incidence of 0.84-1.91 per 100,000 individuals. The syndrome affects both men and women, showing a male preponderance. Campylobacter jejuni, epstein-barr virus, cytomegalovirus, mycoplasma pneumoniae and hemophilus influenzae are amongst the most common causative agents of Guillain-Barré syndrome. Several immunological and genetic factors have been recognised as the risk factors. Human leukocyte antigen, cluster of differentiation 1, and tumor necrosis factor-alpha alleles are among the frequently investigated loci in Guillain-Barré syndrome. Genome-wide association studies have found no significant association of Guillain-Barré syndrome with common variants. Many vaccines against Campylobacter jejuni infection have been proposed, but there are concerns about the efficacy and safety of these vaccines. So far, there is no approved vaccine against Campylobacter jejuni.